Sporadic Fibrodysplasia Ossificans Progressiva in an Egyptian Infant with c.617G > A Mutation in ACVR1 Gene: A Case Report and Review of Literature - Mohammad Al-Haggar; Nermin Ahmad; Sohier Yahia; Amany Shams; Bothina Hasaneen; Rasha Hassan Hassan; Yahya Wahba; Nanees Abdel-Badie Salem; Dina Abdel-Hady (Case Reports in Genetics)
Fibrodysplasia ossificans progressiva (FOP) is an autosomal dominant severe musculoskeletal disease characterized by extensive new bone formation within soft connective tissues and unique skeletal malformations of the big toes which represent a birth hallmark for the disease. Most of the isolated classic cases of FOP showed heterozygous mutation in the ACVR1 gene on chromosome 2q23 that encodes a bone morphogenetic protein BMP (ALK2). The most common mutation is (c.617G > A) leading to the amino acid substitution of arginine by histidine (p.Arg206His). We currently report on an Egyptian infant with a sporadic classic FOP in whom c.617G > A mutation had been documented. The patient presented with the unique congenital malformation of big toe and radiological evidence of heterotopic ossification in the back muscles. The triggering trauma was related to the infant's head, however; neither neck region nor sites of routine intramuscular vaccination given during the first year showed any ossifications. Characterization of the big toe malformation is detailed to serve as an early diagnostic marker for this rare disabling disease.